1992
DOI: 10.1042/cs0830695
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hepatic lipid peroxidation and fibrogenesis in carbon tetrachloride-treated rats: effect of zinc administration

Abstract: 1. Lipid peroxidation and hepatic fibrogenesis were investigated in 25 carbon tetrachloride-treated rats and in 25 control animals. Rats were further divided into two groups to receive either a standard diet or one supplemented with zinc. From each group, animals were killed at weeks 3 and 18 of the experiment for histological and biochemical assessments which included hepatic lipid peroxide and collagen concentrations and plasma zinc concentration as well as the hepatic activities of proline hydroxylase and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 0 publications
4
35
0
2
Order By: Relevance
“…33) Furthermore, a close relationship has been reported between lipid peroxidation and fibrogenesis in rats in which fibrosis was induced by CCl 4 administration. 17,34) Our results confirm the finding that hepatic lipid peroxidation is increased during hepatic fibrogenesis. We also found that FSAP inhibited CCl 4 -induced hepatic lipid peroxidation and consequently attenuated the development of liver fibrosis.…”
Section: Discussionsupporting
confidence: 81%
“…33) Furthermore, a close relationship has been reported between lipid peroxidation and fibrogenesis in rats in which fibrosis was induced by CCl 4 administration. 17,34) Our results confirm the finding that hepatic lipid peroxidation is increased during hepatic fibrogenesis. We also found that FSAP inhibited CCl 4 -induced hepatic lipid peroxidation and consequently attenuated the development of liver fibrosis.…”
Section: Discussionsupporting
confidence: 81%
“…Enzymes scavenging free oxygen radicals (i.e., glutathione reductase and peroxidase, catalase) are decreased during induction of cirrhosis. 20,50,51 In the present study, oxidative stress lasted long after discontinuation of the hepatotoxin and was evident by the increased presence of carbonyl groups in oxidized proteins (Table 3). Acetaldehyde, the main metabolite of ethanol oxidation, increases both collagen production and procollagen mRNA in levels in vitro, an effect blocked by a scavenger of reducing equivalents.…”
Section: Reversing Action Of Adenosine On the Cirrhogenic Effects Of mentioning
confidence: 92%
“…13 Total liver collagen was extracted, as previously described in detail, 13 and quantified by its content of hydroxyproline according to the method reported by Rojkind and González. 18 Subcellular fractionation was performed as reported by Aguilar-Delfín et al 19 Whole homogenate was used to measure activity of prolyl hydroxylase (EC 1.1.1.1) by the technique modified by Camps et al, 20 whereas the cytosolic fraction was the source for assessing thymidine kinase (EC 2.7.1.21) activity according to Sauer and Willmanns. 21 In whole homogenate, lipid peroxidation was estimated by the amount of aldehydic products quantified by the thiobarbituric acid reaction (TBARS), and the rate of protein oxidation by the presence of carbonyl groups, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The addition of zinc in duck diet was effective to be antioxidant that prevent the damage of omega-3 and omega-6 from oxidation process. According to Camps et al (1992), zinc protects fatty acids from peroxidation by inhibiting the production of reactive oxygen species. TBARS value of egg yolk stored at room temperature (29.29 -30.07°C) during 21 days was higher than fresh eggs.…”
Section: Thiobarbituric Acid Reactive Substances (Tbars)mentioning
confidence: 99%